Impact of Ganoderma lucidum fermentation on the nutritional composition, structural characterization, metabolites, and antioxidant activity of Soybean, sweet potato and Zanthoxylum pericarpium residues - Qin Cen; Jin Fan; Rui Zhang; Hongyan Chen; Fuyi Hui; Jiamin Li; Xuefeng Zeng; Likang Qin (Food Chemistry: X, 2024)
One of the major issues in the food sector is the lack of resource utilization and the contamination of the environment caused by by-products. This study aimed to investigate the effects of Ganoderma lucidum (GL) fermentation on the nutritional components, structural characterization, metabolites, and antioxidant activity of soybean residue (SR), sweet potato residue (SPR), and zanthoxylum pericarpium residue (ZPR). The results showed that the nutrient contents of SR, SPR and ZPR increased. The active substances, amino acids (umami, aromatic and basic), metabolites and antioxidant activity (DPPH, ABTS, FRAP) (SR and SPR increased by 11.43, 32.64, 40.19 μmol Trolox/100 g and 19.29, 17.7, 32.35 μmol Trolox/100 g, respectively) of SR and SPR were increased. However, the results of ZPR showed a decrease in the content of bioactive substances, amino acids, and antioxidant activity. The results show that using GL fermentation can provide novel ideas and theoretical basis for improving SR and SPR to obtain new raw materials for antioxidant products.